2021
DOI: 10.1177/17562872211032484
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the impact of marijuana use on semen quality: a prospective analysis

Abstract: Aims: To assess if marijuana consumption – prevalent among men of reproductive age and becoming widespread due to decriminalization – is associated with changes in semen parameters. Marijuana’s active metabolite, tetrahydrocannabinol, can alter signaling pathways within spermatozoa, affecting spermatogenesis and fertility. Methods: We prospectively evaluated semen analyses (SA) from men presenting for infertility evaluation at one institution from July 2017 to April 2018. Participants completed a reproductive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The vast majority of these studies recruited patients with a history of either drug abuse or infertility, thus introducing possible concerns regarding the generalizability of the findings. Hehemann et al [ 24 ] prospectively evaluated the semen analyses from 409 men presenting to medical attention for infertility; 17% of them were current cannabis users presenting with an increased risk of abnormal sperm morphology [odds ratio (OR) 2.15, 95% confidence interval (CI): 1.21–3.79] and decreased semen volume according to the WHO reference standards (OR 2.76, 95%CI: 1.19–6.42). Similarly, Carroll et al [ 25 ] investigated the impact of cannabis use on the semen quality of a population of Jamaican patients attending the infertility clinic for assisted reproduction purpose.…”
Section: Resultsmentioning
confidence: 99%
“…The vast majority of these studies recruited patients with a history of either drug abuse or infertility, thus introducing possible concerns regarding the generalizability of the findings. Hehemann et al [ 24 ] prospectively evaluated the semen analyses from 409 men presenting to medical attention for infertility; 17% of them were current cannabis users presenting with an increased risk of abnormal sperm morphology [odds ratio (OR) 2.15, 95% confidence interval (CI): 1.21–3.79] and decreased semen volume according to the WHO reference standards (OR 2.76, 95%CI: 1.19–6.42). Similarly, Carroll et al [ 25 ] investigated the impact of cannabis use on the semen quality of a population of Jamaican patients attending the infertility clinic for assisted reproduction purpose.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, they found that sample production in summer and Cannabis use in the 3 months before semen collection are associated with teratozoospermia in men aged thirty or less ( 58 ). Another survey of 409 infertile men found that the use of marijuana resulted in abnormal sperm parameters, especially semen volume and sperm morphology ( 59 ). Some other chemicals that correlate with abnormal sperm morphology include exposure to polychlorinated biphenyls, dibenzofurans, and sulfasalazine ( 60 , 61 ).…”
Section: Evidence Synthesismentioning
confidence: 99%
“…The Men's Health Center, located at the University of Washington, conducted a study for infertility evaluation that exhibited a twofold increased risk of strict aberrant morphology [ 29 ]. In comparison to the general population, the prevalence of marijuana usage was 43%, with previous use being more prevalent than the current use.…”
Section: Reviewmentioning
confidence: 99%
“…In comparison to the general population, the prevalence of marijuana usage was 43%, with previous use being more prevalent than the current use. Previous users had the highest chances of strict morphology deficits, indicating a delayed detrimental effect of marijuana on sperm morphology [ 29 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation